THE EFFECTIVENESS OF PLYOMETRIC TRAINING AND RECOVERY MONITORING ON THE PERFORMANCE OF 15-YEAR-OLD SOCCER ATHLETES AT TALENTA FC SOCCER SCHOOL - Septi Hariansyah; zulheri (Journal of Health and Recreation Physical Education (JHRPE), 2026)
This study aims to analyze the effectiveness of plyometric training and recovery monitoring on improving the performance of 15-year-old soccer athletes at SSB Talenta FC. The study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The research sample consisted of 22 athletes selected through a total sampling technique. The training program was conducted for 8 weeks with a frequency of three training sessions per week. The research instruments included the Vertical Jump Test, 20-Meter Sprint Test, Illinois Agility Test, and Yo-Yo Intermittent Recovery Test. Recovery monitoring was carried out through measurements of Rating of Perceived Exertion (RPE), muscle soreness, recovery heart rate, and athletes’ sleep quality. Data analysis utilized normality tests, homogeneity tests, paired sample t-tests, and effect size analysis with the assistance of IBM SPSS version 26. The results showed that plyometric training and recovery monitoring had a significant effect on improving the performance of youth soccer athletes, with the significance value of all variables being 0.000 < 0.05. Performance improvements were indicated by an increase in vertical jump height of 6.54 cm, sprint speed improvement of 0.31 seconds, agility improvement of 1.61 seconds, and aerobic endurance enhancement of 217 meters. In addition, recovery indicators demonstrated improvements through decreased RPE, muscle soreness, and recovery heart rate, as well as enhanced athletes’ sleep quality. It can be concluded that the integration of plyometric training and recovery monitoring is effective in improving the physical performance of youth soccer athletes based on sport science principles